Spillover effects of policy uncertainty on the foreign exchange rate: Evidence from selected developed and developing countries - Md. Shaddam Hossain; Habiba Sultana (Social Sciences and Humanities Open, 2022)
Following the Great Depression of the 1930s, a number of prominent economists believe that the global financial crisis that erupted in 2008 from the American financial market played a significant role in changing the path of global economic progress and intensifying various uncertainties in various market-related activities and processes. Therefore, our research has attempted to quantify how the U.S.‘s economic and monetary policy uncertainty affects the dollar's exchange with its 12 major trading partners, both from developed and developing countries. As part of our analysis, we also factored out the potential impact of the recent global financial crisis—2008. We applied the MM-QR panel conditional quantile regression of Machado and Silva (2019) to the monetary model for exchange rate determination with data from 2000:M1 to 2017:M2. Even though the global financial crisis is under control, the estimated results of the MM-QR panel conditional quantile regression have revealed that the developed countries' economic policy uncertainty, not the U.S.'s economic policy uncertainty, has caused their currencies to depreciate against the U.S. dollar. But the uncertainty of U.S. economic policy has had an asymmetric effect on the exchange rates of developing countries against the U.S. dollar before and after the global financial crisis. Moreover, the U.S.‘s monetary policy uncertainty has depreciated both developed and developing countries' currencies against the U.S. dollar, both with and without control of the global financial crisis. The global financial crisis has also depreciated developing countries' currencies while it has appreciated developed countries' currencies against the U.S. dollar. As a result, this study concludes that whether in developed or developing countries, economic and monetary policy uncertainty has a significant impact on the nominal exchange rate.